Hepatoprotective potential and antioxidant activity of Allium tripedale in acetaminophen-induced oxidative damage - Sahel Ghobadi; Dara Dastan; Meysam Soleimani; Amir Nili-Ahmadabadi (Wolters Kluwer Medknow Publications, 2019)
Allium tripedale (A. tripedale) is a species of wild Allium native to northwest Iran that its hepatoprotective effects have not yet been confirmed. This study investigated the effect of A. tripedale plant against acetaminophen (APAP)-induced acute liver damage. After preliminary studies, the A. tripedale methanol fraction (ATMF) was selected for in vivo study. Thirty-six rats were divided into six groups of 6 each and treated by gavage as follows: groups 1 and 2 received normal saline; group 3 received 400 mg/kg of ATMF; and groups 4-6 were treated with 100, 200, and 400 mg/kg of ATMF, respectively. After two consecutive weeks, except groups 1 and 3, rats were administered with an oral single dose of APAP (2 g/kg). After 48 h, blood and liver samples were collected for histological and biochemical examinations. The results showed that APAP caused a significant increase in alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase and alkaline phosphatase serum levels, lipid peroxidation (all with P < 0.001) and hepatic nitric oxide (P < 0.01). In addition, APAP led to the depletion of the total antioxidant capacity, total thiol group (both with P < 0.001), and structural alterations in the hepatic tissue. Following administration of ATMF extract, a significant improvement was observed in the functional and oxidative stress markers of hepatic tissue alongside histopathologic changes. In conclusion, the present study showed that the administration of ATMF might prevent hepatic oxidative damage by improving oxidant/antioxidant balance in animals exposed to APAP.